Glucopyranoside Dipentanoyl Esters: Synthesis, PASS Predication, Antimicrobial and In Silico ADMET Studies - Matin, M. M.; Chowdhury, S. A.; Bhuiyan, M. M. H.; Kawsar, S. M. A.; Alam, M. A. (Journal of Scientific Research, 2021)
Dimolar pentanoylation of methyl α-D-glucopyranoside using direct method furnished the 2,6-di-O-pentanoate indicating regioselectivity at C-6 and C-2 positions. To develop glucopyranoside based potential antimicrobial agents, 2,6-di-O-pentanoate was further converted into eight newer 3,4-di-O-acyl esters reasonably in good yields. Both prediction of activity spectra for substances (PASS) and in vitro antimicrobial activity test established them as better antifungals than antibacterials. PASS predication also indicated that these sugar esters (SEs) are more potent as anticarcinogenic agents than as antioxidant agents. Structure activity relationship along with in silico ADMET studies clearly indicated that combination of pentanoyl (C5) and lauroyl (C12) in the glucopyranoside framework could be a potential antifungal agent especially against Macrophomina phaseolina.